A Single-Ended Protection Scheme for Flexible HVdc Transmission Lines Based on the Fréchet Distance of the Rate of Change of Fault Voltage Traveling Waves - Hui Qin; Faxi Peng; Zhen Pan; Yilin Zhong; Tao Liu; Runbin Cao (IEEE Access, 2025)
Flexible DC transmission technology is a technical solution for the large-scale integration of renewable energy. To ensure the stable operation of transmission systems, the rapid and selective protection of transmission lines is crucial. However, the existing traveling wave (TW) protection methods have several main problems, such as insufficient tolerance to fault resistance at the remote ends. To address this problem, a protection scheme based on the overall curve characteristics of TWs is proposed. Specifically, a mathematical analysis is conducted on the initial line-mode TW curves, focusing on the differences between the rate-of-change characteristics exhibited by the initial TW under internal and external faults. On the basis of the analyzed mathematical expression, the reference curves of the rate-of-change of traveling waves (ROCOTW) under internal and external faults are subsequently established. The Fréchet distance (FD) is used to quantify the similarity between the reference and the measured curves of the ROCOTW. If the FD between the measured curve and the internal fault reference curve is less than the FD between the measured curve and the external fault reference curve, the simulated fault is determined to be an internal fault. Otherwise, it is determined to be an external fault. Finally, the results show that the proposed scheme can tolerate a fault resistance of $\,600{Ω }$ and 35 dB of noise under different grid topologies and a current-limiting reactor (CLR) of 70 mH. This scheme can quickly and accurately distinguish between internal and external faults.